Caracterizaç\~ao do fluxo de cargas e indicadores de concorrência entre os portos Brasileiros - Alexandre Ywata de Carvalho; Paulo C. Coutinho; André L. Oliveira; Paulo Augusto P. de Britto; Paulo Roberto Barbosa Lustosa (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– In this paper, we characterize the domestic cargo flows for imports and exports, from and towards the Brazilian ports. Based on this characterization, it is possible to calculate basic competitiveness indicators, for different cargo types. We also present a discussion on minimum efficient scales for port operations. This discussion is particularly important for regulatory policies, because ports within geographic markets with little demand can accommodate only one terminal, without increasing marginal costs and prices. We observed that the geographic factor seems to be extremely important in determining which port to use to export Brazilian products or to import foreign cargo. In general, port competition seems to be more pronounced in federation states away from the coast. For states on the coast, exporting and importing companies seem to choose ports within their own states or in neighboring federation units. The great importance of the geographic proximity may be directly related to the high surface transportation costs observed in Brazil.
Keywords: L11; L13; L52; L91; R42; R12; 330; port sector; geographic markets; hinterlands; competitiveness indicators; minimum efficient scale